THE INFLUENCE OF SERVICE QUALITY AND TAX LITERACY ON TAXPAYER COMPLIANCE MODERATED BY TAX SANCTIONS: THE INFLUENCE OF SERVICE QUALITY AND TAX LITERACY ON TAXPAYER COMPLIANCE MODERATED BY TAX SANCTIONS - Rum, Hijriyati; Munthe, Richa Afriana; Supeno, Bambang; Burhan , Burhan (PENANOMICS: International Journal of Economics, 2024)
Taxpayer compliance is the key to achieving optimal state revenue goals. The quality of service provided by tax agencies greatly influences the level of compliance, because good service can increase taxpayer trust and comfort. This is due to various things, including service quality, tax literacy, taxpayer compliance and tax sanctions. The purpose of this study is to analyze the effect of service quality on taxpayer compliance of two-wheeled motor vehicles, the effect of tax literacy on taxpayer compliance of two-wheeled motor vehicles, the effect of tax sanctions moderating the relationship between service quality and taxpayer compliance of two-wheeled motor vehicles, the effect of tax sanctions moderating the relationship between literacy and taxpayer compliance of two-wheeled motor vehicles. The research method is quantitative with descriptive explanation, this study uses a sample of 196 employees and data processing using SEM PLS. The research findings show that 1) service quality has a positive effect on taxpayer compliance of two-wheeled motor vehicles 2) tax literacy has a positive effect on taxpayer compliance of two-wheeled motor vehicles 3) tax sanctions moderate the relationship between service quality and taxpayer compliance of motor vehicles 4) tax sanctions moderate the relationship between literacy and taxpayer compliance of two-wheeled motor vehicles at the Rengat Revenue Management UPT